A Gateway to Learning: Exploring the Role of Campus Recreation and Leisure Experiences in Developing a Sense of Purpose in African American Males at a PWI. Issue 2 (October 2019) - Patterson, Anthony F.; Dorwart, Catherine E.
Personal, social, and cultural issues influence any student's ability to succeed in college, but these issues are more pronounced for African American males from low socioeconomic status (SES) backgrounds attending predominantly White institutions (PWIs). Since campus engagement, recreation, and leisure can play pivotal roles in a student's experience, investigating their influence relative to social integration might facilitate better understanding of the contemporary issues these students face. The purpose of this study was to explore how African American male undergraduates from low SES backgrounds perceived leisure and the role that campus engagement played in their social integration at a PWI. Seventeen African American male undergraduates from low SES backgrounds were interviewed. While several themes emerged, this article focuses on discovering a sense of self and navigating campus cultures . This research demonstrated that recreation and leisure spaces were instrumental in developing a sense of purpose for the young men at this PWI.